Some Observations on Butterflies of Pakke Tiger Reserve, Arunachal Pradesh - Sebastian, Jis; Pachoni, Arindam K. (Indian Forester, 2012)
Butterfly diversity was documented first time in and around Pakke Tiger Reserve, Arunachal Pradesh, during autumn. 65 species with in 43 genera representing 14 sub families within 5 families were recorded during the present study. Jaccard's similarity index showed greater dissimilarity of butterfly fauna between forest edge and forest habitats and also within families at two sites. This may be due to the difference in vegetation composition and disturbances at two sites. Out of the 65 recorded butterflies 12 species enjoys a legal protection by Indian Wildlife Protection Act and CITES.